Artemisia scoparia: A new source of artemisinin - Singh, Aditi; Sarin, Renu (Bangladesh Journal of Pharmacology, 2010)
Artemisinin is considered as the most active and potent antimalarial drug. Till date Artemisia annua Linn. plant is the only source for its production The present investigation was carried out with an objective to search a new plant for artemisinin. An attempt was made on a perennial faintly odoratus herb, Artemisia scoparia Waldst et Kit. to find out an alternative of A. annua for the production of artemisinin. The yield of artemisinin was higher in aerial plant parts (0.015%) in comparison to callus culture (0.001%). The present study concluded that A. scoparia contains an antimalarial drug artemisinin.